Examining the jurisprudential ruling on "Astrology and its teaching and learning" from the perspective of contemporary jurisprudence - Rashidi, Azar (2021)
"Tanjim" means "belief in the effect of the state of the constellations and the movement of stars in human life and terrestrial events" is one of the topics that have long been of interest to humans, including Muslims. The existence of some narrations, for or against this issue, has caused the jurists of Islamic religions to disagree about its permission or sanctity. As far as it is mentioned in Shiite jurisprudential books as one of the forbidden achievements. The issues related to the jurisprudential ruling of Tanjim can be examined in four areas; The principle of entering the discussion of stars and astronomy; Teaching and learning it; Practice it; and acquire it. In this research, in a descriptive-analytical manner, with the information obtained from the library method, and by analyzing the narrations, we examine the arguments of the jurists of the two sects in the second area. Research findings show that; The teaching of astrology is permissible and sometimes recommended if it means astronomy and cosmology. However, it is forbidden if it requires other prohibitions, such as believing in the independent influence of the stars in terrestrial events, or their association with God, lying, or foretelling suspicious matters.